A Case Report on Bilateral Adrenal Histoplasmosis (Bangladesh Journal of Urology, 2020)
Disseminated histoplasmosis affecting the adrenal glands is a very rare infection and an uncommon cause of adrenal insufficiency. We present a case of bilateral adrenal histoplasmosis in a 77 years old immunosuppressed patient who presented with bilateral adrenal masses. The fine needle aspiration cytology of the adrenal mass was positive for Histoplasma capsulatum.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.210-212